Bimbingan al-Quran dengan Metode Tartil bagi Santri - Agus Zainudin; Risalatul Qomariyah (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2022)
Al-Qur'an Education Park is a non-formal education in Sumber Lesung Village, Ledokombo District, Jember Regency. In the TPQ, learning to recite the Qur'an using the tartil method is very important because the tartil method in addition to Allah's commands, is also one of the four types of reading according to qiro'at experts. The place of service is in the al-Qur'an Education Park (TPQ) at the Al-Baitul Muhibbin mosque in Karang Bireh Hamlet, Sumber Lesung Village, Ledokombo District, Jember Regency, which is determined by the purposive area technique, while in determining the informants using purposive sampling technique. The implementation of al-Qur'an guidance with the Tartil method at the TPQ of the Al-Baitul Muhibbin mosque, Karang Bireh Hamlet, Sumber Lesung Village in general went well. The implementation of guidance is carried out by: (1) Preparing, (2) Implementation, (3) evaluation. The development of the ability to read the Qur'an of students is very good although there are still obstacles such as: they still prefer to play, joke, and the background abilities of those who are different but these obstacles can still find a good solution, for example: providing direction more intense, giving punishments that educate to be more disciplined in following the guidance of the Qur'an.